CO2 as a soft oxidant for propane oxidative dehydrogenation: A mechanistic study using operando UV Raman spectroscopy. Issue 50 (August 2021) - Rogg, Simone; Hess, Christian
Graphical abstract: Highlights: Mechanistic study of propane ODH using CO2 as oxidant over VOx /SiO2 catalysts. Operando UV Raman spectroscopy reveals structural dynamics during ODH reaction. Reduction and fragmentation of surface vanadia species under reaction conditions. Mechanism follows parallel propane ODH and two-step propane DH/rWGS reaction. Abstract: The utilization of CO2 as an oxidant has recently attracted increasing attention due to its mild oxidizing properties allowing higher product selectivities to be achieved e.g. in propane oxidative dehydrogenation (ODH). In this communication we address mechanistic aspects of propane ODH over silica supported vanadia (VOx /SiO2 ) catalysts in the presence of CO2 as oxidizing agent. The use of operando UV Raman spectroscopy reveals distinct changes in the surface vanadia structure including breakage of VOV bonds and a partial reduction of vanadyl, as well as the formation of support hydroxyl groups, while the presence of CO2 is observed to prevent coke deposition. Our results are fully consistent with the occurrence of two parallel pathways, i.e., direct ODH (one step) and dehydrogenation followed by a reverse water-gas shift reaction (two step), supporting previous literature proposals.